Radikalisme Versus Islam Rahma - Abbas Abbas (LPPM IAIN Sorong, 2015)
Islamic doctrine is viewed as rahmatan lil alamin. But it still needs big question. Then it is not only based on the application aspect, but also rahmatan lil alamin’s consept. Besides as academic intelectual activities, quarrying the rahmatan lil alamin’s consept, this information era, also by the future observer state that involvement of the academic intelectual workings urgent dan to be needed to overcome the life’s problems nowadays. So radicalism and terrorism in this view, are not separated with rahmatan lil alamin of Islamic doctrine views. This writing discourses the central theme, namely; As Islamic doctrine andits relevance of local wisdem, how is the rahmatan lil alamin’s consept. The study answers questions: First, what are radicalism and terrorism term? Second, as a big Islam vision or mision, how is the Rahmatan lil alamim’s concept? Thirt, how is the local wisdem (Bugisness’s ethnic) as culture basis humanity? Fourth, how is the local culture development and Islam in the context of amar makruf nahi munkar: terrorism and radicalism bid to prevention?. The last, this writing gives birth to viewings that Islam concept is rahmatan lil alamin, have views about humanity, freedom of expression, wisdom, ect.